Food Consumption Habits and Nutritional Status of Women and Infants - Pokharel, Tanka Maya (Journal of Health Promotion, 2019)
This paper attempts to find-out the existing knowledge of nutrition on food consumptions and dietary practices of women and infants. I have used the systematic review of the Hinari database which were published from 2012 April to 2018.These data show that women and infant food consumption behaviour and nutrition status is directly related to family food consumptions. Research shows that low cobalamin and folic acid was found in women before they conceive and folate deficiency was uncommon on food consumptions. Low intakes of iron are consistent with a high prevalence of an aemia seen in the six to twenty-four months of children. Food beliefs and practices tend to reduce women’s consumption of micronutrient-rich foods, such as dietary restrictions during menstruation, pregnancy and lactation. The research shows that are overlapping with these beliefs and practices on intra household allocation of food. The poor dietary practice among pregnant women which ranges from 39.3 percent to 66.1 percent have limited nutritional knowledge and wrong perception towards dietary behaviour. It was also found that basis underweight is greater in rural areas (31 percent) than in urban areas (23 percent). Those children whose mothers are illiterate are more than twice as likely to be underweight than the children whose mothers have at least basic education.